2011
DOI: 10.4258/hir.2011.17.1.67
|View full text |Cite
|
Sign up to set email alerts
|

New Integrated Information System for Pusan National University Hospital

Abstract: ObjectivesThis study presents the information system for Pusan National University Hospital (PNUH), evaluates its performance qualitatively, and conducts economic analysis.MethodsInformation system for PNUH was designed by component-based development and developed by internet technologies. Order Communication System, Electronic Medical Record, and Clinical Decision Support System were newly developed. The performance of the hospital information system was qualitatively evaluated based on the performance refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
0
6
0
2
Order By: Relevance
“…System response time is a major technical challenge of the HIS [28,62]. The dissatisfaction with this domain highlighted in numerous studies was reported as an obstacle to applying EHRs and the main reason for their abandonment by users [62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…System response time is a major technical challenge of the HIS [28,62]. The dissatisfaction with this domain highlighted in numerous studies was reported as an obstacle to applying EHRs and the main reason for their abandonment by users [62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…System response time is a major technical challenge of the HIS [28,62]. The dissatisfaction with this domain highlighted in numerous studies was reported as an obstacle to applying EHRs and the main reason for their abandonment by users [62][63][64]. Organizations that heavily depend on computerized systems to deliver patient care require downtime as low as 0% and business continuity procedures to ensure safety and patient care continuity [65].…”
Section: Discussionmentioning
confidence: 99%
“…Input/Output of measurement process Royer and Wolfgang [40] I = intangible benefits in the financial, security/risk mgmt., supporting processes and business processes, O = measurements Grembergen and Amelinckx [13] I = survey(s) with questions in the area of customer orientation, business contribution, customer orientation, operational excellence, and future orientation O = measurements KPI is used as one way of transforming the intangible benefits to tangible [12,24], see Table 7. The starting point for both these articles is to understand the KPI for the desired output.…”
Section: Articlementioning
confidence: 99%